Perspektif dan Pengalaman Guru Bahasa Inggris dalam Mengajar Bahasa Inggris Lintas Minat - Tartila, Tartila (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Since the issuance of the 2013 curriculum (K13), many Islamic senior secondary schools (MA) offer English as Cross Interest Subject (EaCIS) in addition to compulsory English subject (CES). The subject is designed to help students expand their English language competence beyond their major courses and what they have learnt from CES. Due to a reduction in the number of hours allocated for CES in the K13, teaching EaCIS has become a way for certified English language teachers to accrue the required hours to receive certification payment. This qualitative study was designed to understand teachers' perceptions and experiences of teaching EaCIS and shares the findings from the interview and focus group data collected from six English language teachers teaching at state Islamic senior secondary schools (MAN) in Indonesia. Findings reveal that whilst EaCIS provides an opportunity for teachers to improve student's English abilities, none of the participants received support to teach it. Whilst it is acknowledged that this is a small study and the findings cannot be generalised to the broader population of teachers responsible for teaching EaCIS, the experiences shared by participants provide valuable and interesting insights into curriculum change. Recommendations for improving the implementation of EaCIS and the future design of curriculum change initiatives in Indonesia are discussed.Keywords: English as Cross Interest Subject, teacher experiences, teacher perceptions, curriculum change, K13 curriculum